Loyalitas Karyawan ditinjau dari Kualitas Kehidupan Kerja pada Karyawan dan Karyawati - Edwin Lau; Rianda Elvinawaty; Ahmad Irvan Dwi Putra (Mahesa Research Center, 2019)
The focus of this research is the relationship between quality of work life with employee loyalty to employees at PT. Indako Trading Coy, Medan. The purpose of this study was to determine and analyze the relationship of quality of work life with employee loyalty to employees at PT. Indako Trading Coy, Medan. The method in this research is quantitative. The research hypothesis is that there is a positive relationship between the quality of work life and employee loyalty. Data collection techniques are using scale techniques where there is a scale distribution to measure the quality of work life towards employee loyalty. The type of scale used is the Likert Scale. The results of this study are a positive relationship between the quality of work life and employee loyalty to employees and employees at PT. Indako Trading Coy Medan with a Product Moment correlation (r) of 0.626 with p of 0.000 (p <0.05), meaning the higher quality of life work, the higher the loyalty of employees, on the contrary if the lower the quality of work life, the lower the loyalty of employees.